American Reform Judaism : an Introduction. - Kaplan, Dana Evans (Rutgers University Press, 2003)
The only comprehensive and up-to-date look at Reform Judaism, this book analyzes the forces currently challenging the Reform movement, now the largest Jewish denomination in the United States. As an unintended result of its success, the movement now struggles with an identity crisis brought on by its liberal theology. Kaplan asks, can Reform Judaism continue to thrive? Can it be broadly inclusive and still be uniquely and authentically Jewish? Addressing the issues that have confronted the movementincluding the ordination of women, acceptance of homosexuality, the problem of assimilation, the.